2019
DOI: 10.1002/jso.25599
|View full text |Cite
|
Sign up to set email alerts
|

Systemic chemotherapy and survival in patients with metastatic low‐grade appendiceal mucinous adenocarcinoma

Abstract: Background Appendiceal cancer is a rare malignancy that exhibits a wide range of histology and treatment response. Given the rarity and heterogeneous nature of the disease, it has been difficult to define optimal treatment strategies. Our goal is to examine the association between use of systemic chemotherapy and survival in patients with metastatic low‐grade mucinous appendiceal adenocarcinoma. Methods The National Cancer Database (2004‐2015) was queried, and patients with mucinous, grade 1, stage IV appendic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Kolla et al recently reported that in a study of 103 patients with appendiceal adenocarcinoma, adjuvant chemotherapy following complete cytoreduction significantly improved overall survival compared to cytoreduction alone [ 12 ]. In contrast, other studies reported no beneficial effect of chemotherapy in the treatment of appendiceal adenocarcinoma [ 6 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Kolla et al recently reported that in a study of 103 patients with appendiceal adenocarcinoma, adjuvant chemotherapy following complete cytoreduction significantly improved overall survival compared to cytoreduction alone [ 12 ]. In contrast, other studies reported no beneficial effect of chemotherapy in the treatment of appendiceal adenocarcinoma [ 6 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 92%
“…Though surgery is the first option in the treatment of appendiceal cancer, chemotherapy has been applied using a protocol similar to that used to treat colorectal cancer [ 3 , 4 ]. The rarity and high heterogeneity make it difficult to examine the effect of chemotherapy in treatment of appendiceal cancer in systematic studies [ 5 , 6 ]. Most previous studies had a limited sample size from a single institution, and only included certain histological types [ 7 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 13 , 16 , 32 This distinction has important clinical implications, given that low-grade AA tend to be unresponsive to traditional cytotoxic chemotherapy and in light of a recent large retrospective analysis ( N = 639) showing no association of chemotherapy with improved OS. 34 Additionally, new guidelines from the American Society of Colon & Rectal Surgeons now suggest avoiding chemotherapy for low-grade AA. 35 …”
Section: Discussionmentioning
confidence: 99%
“…No clear benefit when using bevacizumab was observed in this report, with a trend towards longer OS in non-bevacizumab regimens (p = 0.41) and significant results in PFS favouring bevacizumab-free regimens (p = 0.01) [13]. A recent retrospective review of 639 patients with well-differentiated metastatic appendiceal adenocarcinoma achieved significant results in terms of OS for patients who underwent initial surgery (HR 0.40, 95% CI 0.28-0.57) and also for female sex, but not in the case of patients receiving chemotherapy (HR 1.1, 95% CI 0.56-0.94), probably related to a slow cell growth with less chemotherapy activity in this subgroup [14]. A non-significant trend towards an increase in 5-year OS was observed for chemotherapy versus observation (61.3 vs. 52.9%, respectively).…”
Section: Discussion/conclusionmentioning
confidence: 93%